IMPLEMENTASI APLIKASI SUKMA SANTRI SEBAGAI WADAH DALAM UPAYA MENDUKUNG PENINGKATAN PENILAIAN KUALITAS PELAYANAN PUBLIK DI BAGIAN UMUM SEKRETARIAT DAERAH KABUPATEN JOMBANG - Rahmawati, Biwin; Nafi’ah, Binti Azizatun (Jurnal Progress Administrasi Publik, 2024)
In this study the Implementation of the Sukma E-Santri Application in the General Section of the Regional Secretariat of Jombang Regency, that government cannot be separated from the quality of public services as an effort to evaluate the performance that has been provided, therefore this application is implemented which refers to the e-government system to make it easier to provide an assessment of the quality of government performance on services provided to the community and realize quality that is fast, effective, efficient and transparent. This research took place at the General Section Office of the Regional Secretariat of Jombang Regency. Data collection was carried out from the results of observations, the internet, interviews from the Head of the General Section TU Subdivision, employees and the public. The data obtained was then combined, processed and analyzed using qualitative methods. The method in this study refers to the George C Edward III implementation model. Assessment of the quality of public services with this application is a reference so that the services provided are getting better in the future and the community is expected to participate in its implementation. The results of the study state that the application of this application from the George C Edward III policy model from the aspects of communication, resources, disposition and bureaucratic structure has shown good results, it's just that there are some that need to be addressed from the quality of performance provided to the community, then the lack of socialization and assistance to the community so that there are some people who take it for granted, and the implementation of the Sukma E-Santri application has a positive influence on the quality of employee performance.   Keywords: Implementation; Public Service; E-Government